The Space-Exposed Kombucha Microbial Community Member Komagataeibacter oboediens Showed Only Minor Changes in Its Genome After Reactivation on Earth - Santana de Carvalho, Daniel; Trovatti Uetanabaro, Ana Paula; Kato, Rodrigo Bentes; Aburjaile, Flávia Figueira; Jaiswal, Arun Kumar; Profeta, Rodrigo; De Oliveira Carvalho, Rodrigo Dias; Tiwar, Sandeep; Cybelle Pinto Gomide, Anne; Almeida Costa, Eduardo; Kukharenko, Olga; Orlovska, Iryna; et al. (Frontiers in Microbiology, 2022)
In our recent reports, we have shown that Komagataeibacter is the dominant taxon and cellulose producing bacteria. This is the first study to isolate the K. oboediens genome from reactivated space-exposed KMC (Kombucha Microbial Community) sample and comprehensively characterize it. The space-exposed genome was compared with the Earth-based reference genome to understand the genome stability of K. oboediens under extraterrestrial conditions. Our results suggest that the genomes of K. oboediens IMBG180 (ground sample) and K. oboediens IMBG185 (space-exposed) are remarkably similar in topology, genomic islands, transposases, prion-like proteins, and number of plasmids and CRISPR-Cas cassettes. Nonetheless, there was a difference in the length of plasmids and the location of cas genes. Small difference was observed in the number of protein coding genes. Despite these differences, they do not affect any metabolic profile including cellulose synthesis, nitrogen-fixation, hopanoid lipids biosynthesis, and stress-related pathways. Minor changes are only observed in central carbohydrate and energy metabolism pathways gene numbers or sequence completeness These findings suggest that K. oboediens maintains its genome stability and functionality in KMC exposed to the space environment. Furthermore, K. oboediens may be used to develop a safe drink for space travel with minimal microbial composition of KMC. Moreover, due to its unaffected metabolic pathways, this bacterial species may also be used for cellulose biosynthesis and nitrogen-fixation related space experiments.